EFFICACY OF CHLORIMURON ALONE AND IN MIXTURE WITH QUIZALOFOP-P-ETHYL AGAINST WEEDS IN SOYBEAN [ YBEAN [GLYCINE MAX (L.) MERRILL] (L.) MERRILL] - AHIRWAR, PREETI; MALVIYA, POORNIMA; VIJAY SURYAWANSHI, M. L. KEWAT (The Bioscan, 2016)
A field experiment was conducted during Kharif season of 2008 at Livestock Farm, JNKVV, Jabalpur to study the efficacy of chlorimuron alone and in mixture with quizalofop-p-ethyl against weeds in soybean (Glycine max (L.) Merill). The field was mainly infested with monocot weeds like Echinocola colona, Dinebra retroflexa and Cyperus iria. Dicot weeds Alternanthera philoxeroides and Eclipta alba were less dominant in soybean ecosystem. The efficacy of chlorimuron alone as post-emergence was poor when applied @ 6g/ha in reducing weed density and dry weight which was improved slightly with increase the herbicide dose to 9 and 12 g/ha. Among the herbicides combinations, application of chlorimuron+quizalofop-p-ethyl+vit-o-vit @ 9+75+750 g/ha was most effective in reducing weed growth and it gave highest weed control efficiency (53.51 and 80.52%), crop biomass (591.99 g/m2) than that of application of chlorimuron @ 6,9 and 12 g/ha and its mixture with quizalofopp-ethyl @ 50 g/ha and imazethapyr @75g/ha. The significantly highest yield attributing characters were obtained under combined application of chlorimuron+quizalofop-p-ethyl+vit-o-vit @ 9+75+750 g/ha over rest of the treatments. Treatment of hand weeding twice at 20 and 40 DAS check the weed growth and recorded significantly highest seed yield (1.62t/ha) which were at par with the combined application of chlorimuron+quizalofopp-ethyl+vit-o-vit @ 9+75+750 g/ha